COVID-19 and respiratory support devices (2020)
There are significant logistical challenges to providing respiratory support devices, beyond simple oxygen flow, when centres run out of supplies or do not have these devices at all, such as in low resource settings. At the peak of the COVID-19 crisis, it was extremely difficult to import medical equipment and supplies, because most countries prohibited the medical industry from selling outside of their own countries. As a consequence, engineering teams worldwide volunteered to develop emergency devices, and medical experts in mechanical ventilation helped to guide the design and evaluation of prototypes. Although regulations vary among countries, given the emergency situation, some Regulatory Agencies facilitated expedited procedures. However, laboratory and animal model testing are crucial to minimize the potential risk for patients when treated with a device that may worsen clinical outcome if poorly designed or misused.